Peningkatan keterampilan melalui pelatihan penanaman Tanaman Toga di Dusun Jambon, Babadan, Kecamatan Sambi, Kab Boyolali - Rozak, Ilham Fatku; Musyary, Muhammad Fazis; Ramadhani, Diana Dwi (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Family Medicinal Plants (TOGA) is a program that utilizes land in the yard, garden, or field to grow plants with healing properties or medicinal uses. In this community service, the main target community is PKK mothers in Jambon Hamlet, Babadan, Sambi District, Boyolali Regency. This service program aims to increase the knowledge and skills of housewives about the benefits and functions of TOGA scientifically and improve skills in planting family medicinal plants. The training is carried out by providing facilities and infrastructure for service activities to improve the community's ability and skills in TOGA management. The majority of participants achieved a high level of knowledge represented by 11 people. The results of this service program have shown positive results in improving the communities' ability and skill in managing TOGA. In addition, the ease of planting and maintaining these plants, coupled with the fertile condition of the village land makes TOGA cultivation feasible and promising.